Reliability of Cast Index for Dental Caries Detection (Medical Forum Monthly, 2024)
Objective: To access the inter-examiner reliability of CAST (Caries Assessment Spectrum and Treatment) index for detecting dental caries status among patients visiting a public sector dental hospital of Karachi, Pakistan.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted in the dental diagnostic outpatient department of a public sector dental hospital, Karachi, Pakistan, over a period of one month from September 2013 to October 2013Materials and Methods: Selected/consented participants were examined for dental caries status by the two trained and calibrated examiners using CAST index. A structured and validated proforma was used to record the findings. The inter-examiner reliability was undertaken to find out the reproducibility of this novel method of caries examination. Data entry and analysis was done using SPSS software at 5% level of significance. Descriptive statistics were performed that involved the frequencies of age and gender. Inter-examiner reliability of CAST was assessed using percentage agreement and Cohen's Kappa value.Results: A total of 100 subjects were recruited for the present study. There were 63% females and 37% males with a mean age of 31±17 years. The percentage agreements obtained for the two examiners were between 70-100% for 9 different codes of the CAST index. The Cohen's Kappa value identified was 0.99.Conclusion: A strong inter-examiner reliability has been observed for scoring the CAST index which exemplifies the entire patho-physiological phases of dental caries. Results of this study substantiate the potential of CAST index for reproducibly scoring the enamel, dentine and pulp lesions.